The two-state solution from the point of view of the Israeli right - Ewaiwi, Mohammed Asaad Diab (Arab Journal for Sciences and Research Publishing, 2022)
Through the historical tracing of the position of the Israeli right towards the two-state solution, it becomes clear to us that it adopted the settlement vision of the Labor Party, and this was embodied in the adoption of the double column plan that was planned and discussed in the Labor government and was supervised by Sharon, which combines the two settlement visions of Dayan and Allon, and the right rejected The principle of establishing a Palestinian state according to the model of the two-state solution. It is noted through the initial reading of the current situation that the right-wing and extreme right-wing parties enjoy a broad and basic presence in the Israeli political scene. In terms of relations with the Palestinians and the two-state solution, the Bennett Lapid government has little to offer, as the two-state solution is no longer within the plans of Israeli society or the government. In the absence of an integrated Israeli project for a political solution with the Palestinians, and the rejection of the two-state solution and the one-state solution, respectively, future Israeli steps are directed more towards implementing a mixture of the one-state solution and the two-state solution. This mixture that is forming will certainly not result in the two-state solution or the one-state democratic solution. Rather, it will open the door to a mixed mixture of these two solutions in the form of a "state of the state", ie isolated and torn Palestinian areas that lack sovereignty and control over land and population and are under full Israeli sovereignty. In this case, Israel wants to benefit from the advantages of the mixed solution and get rid of the disadvantages of the two-state solution.